Some physical and mechanical properties of Laminated Veneer Lumber reinforced with glass fiber mesh - Bekir Cihad Bal (Maderas: Ciencia y Tecnología, 2023)
Structural composite lumbers are used extensively in wooden structures. There are many reasons for choosing these materials, including their light weight, easy assemble, and low cost. Various studies have been conducted to increase the load carrying capacities of these materials. Reinforcement with various natural or synthetic fibers is one method that has been studied. In this study, laminated veneer lumber was produced using poplar veneers and glass fiber mesh. One-component polyurethane glue was used in the production of the boards. The modulus of rupture, modulus of elasticity in bending, impact bending strength, and splitting strength values of the control laminated veneer lumber and laminated veneer lumber reinforced with the glass fiber mesh were investigated. In addition, some physical properties such as the densities and moisture contents of the test samples were investigated. Although the reinforcement of laminated veneer lumber using glass fiber mesh had statistically significant effects on impact bending strength, and splitting strength. The effect on the modulus of rupture and the modulus of elasticity in a static bending test was not significant. In addition, the effects of the reinforcement on the densities and moisture contents of the test samples compared the control samples were statistically significant.